2020
DOI: 10.1177/1758573220950235
|View full text |Cite
|
Sign up to set email alerts
|

Quotation errors related to the Proximal Fracture of the Humerus Evaluation by Randomization (ProFHER) study

Abstract: Aim The aim of this study was to assess the accuracy of quotations of the Proximal Fracture of the Humerus Evaluation by Randomization (ProFHER) study in the published literature. Methods A literature search was performed from March 2015 to November 2019 to identify all papers that reference ProFHER since its publication. Full text articles were reviewed by two independent reviewers using a validated framework of assessing quotation errors. A kappa co-efficient was calculated to assess interobserver reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Our findings are consistent with previous investigations over the past decade within the orthopaedic trauma, hand, sports, foot and ankle, and pediatric specific literature, with identified quotation errors rates ranging from 7.6% to 38%. 1 , 2 , 3 , 4 , 5 , 6 , 7 More broadly within the biomedical literature, others have identified citation inaccuracy as a problem, including reference quotation errors within anatomy, neurosurgical spine, otolaryngology, and burn journals. Within this body of literature, quotation error rates have been found to range from 13.7% to 19%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous investigations over the past decade within the orthopaedic trauma, hand, sports, foot and ankle, and pediatric specific literature, with identified quotation errors rates ranging from 7.6% to 38%. 1 , 2 , 3 , 4 , 5 , 6 , 7 More broadly within the biomedical literature, others have identified citation inaccuracy as a problem, including reference quotation errors within anatomy, neurosurgical spine, otolaryngology, and burn journals. Within this body of literature, quotation error rates have been found to range from 13.7% to 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Prior evaluations of the orthopaedic peer-reviewed literature suggest citation error rates of 7.6% to 38%. 1 , 2 , 3 , 4 , 5 , 6 , 7 However, relatively little attention has been paid to citation errors in sports medicine journals specifically. Additionally, the methodology of reference review employed in the existing literature often relies on a subsample of references.…”
mentioning
confidence: 99%
“…Another article examined quotation errors related to a specific hand-surgery-related article (Knirk and Jupiter, 1986) and found that 63 of 154 articles (41%) that referenced the original article contained at least one error (Porrino et al, 2008). A previous article from our institution (Bagga et al, 2020) assessed quotation errors related to the PROximal Fracture of the Humerus: Evaluation by Randomisation (PROFHER) trial (Rangan et al, 2015) and showed an overall error rate of 13%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, misinterpretation of statistical significance in abstracts can result in overstated or unjustified conclusions. Additionally, studies have demonstrated inaccurate citation practices across various medical and surgical specialties, including different orthopaedic surgery subspecialties [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%